The ClassDojo – a virtual window - Chambel, Ana Almeida (Revista da UI_IPSantarém, 2020)
This article reports how a group of educators and primary teachers in Agrupamento de Escolas de Sampaio, in Sesimbra, invented in a collaborative way, a way to reach students, many of them from families without contact with technology. The study presents the use of the educational platform, ClassDojo, that uses common dynamics and characteristics in gamification environments, to promote communication between members of the educational community, helping teachers to manage and encourage positive behaviors in the classroom and to build activity guides for home in distance learning situations. It is a platform that depends on the dynamics of the relationship between users, a feature common to games that in this case is used for educational purposes. In order to obtain the results of this study, a survey was carried out by questionnaire to all primary teachers and educators in the group, after which some interviewees were interviewed in order to assess the benefits and difficulties in using this tool and what repercussions this moment had on the work dynamics of this group.